Internet connectivity disruption in Venezuela (Venezuela) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Venezuela. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: VE-2026-0267. Severity: critical. Confidence: 65%